INCLISIRAN (LEQVIO): A FIRST-IN-CLASS SMALL INTERFERING RNA THERAPEUTIC DRUG APPROVED BY FDA FOR TREATING PRIMARY HYPERCHOLESTEROLEMIA OR DYSLIPIDEMIA - VENUNGOPAL, PRIYANKA; BALAKRISHNAN, KARTHIKEYAN; SRIRAM, DAMAL KANDADAI; GEORGE, MELVIN (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Elevated levels of low density lipoprotein (LCL) – cholesterols are an established risk factor for the development and progression of cardiovascular diseases, particularly atherosclerosis. Statins are the first-line treatment for dyslipidemia which helps in lowering lipid levels (bad cholesterol). Although statin therapy is a conventional and gold-standard method, some patients who have high cardiovascular risk are either intolerant to statins or have persistently elevated LDL levels despite receiving highest dose of statin. Therefore, for such patients, proprotein convertase subtilisin/ kexin Type 9 (PCSK9) inhibitor drugs are recommended. This review highlights the importance of PCSK9 inhibitors, focusing mainly on the recently approved (Food and Drug Administration) first-in-class small interfering RNA therapeutic drug called inclisiran (Leqvio) developed by Novartis. The article also summarizes the safety and efficacy of inclisiran based on the ORION clinical trials, benefits, and cost-effectiveness over other previously approved PCSK9 inhibitor drugs.